2001
DOI: 10.1080/02652030110053660
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium, mercury, iron, copper, manganese and zinc in the liver and kidney of the Icelandic lamb

Abstract: The purpose of this study was to evaluate the levels of cadmium, mercury, iron, copper, manganese and zinc in lamb liver and kidney from six areas in Iceland and to compare the results against aerial deposition data for the same elements obtained using moss as an indicator organism. The total number of samples was 96 for each organ. Cadmium was determined by graphite furnace atomic absorption spectrophotometry, mercury by cold-vapour atomic absorption, and iron, copper, manganese and zinc by inductively couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…This phenomenon could explain why, despite the remoteness and low industrial activity in northeastern Iceland, MeHg concentrations in terrestrial arthropods are elevated, although it is unclear why MeHg concentrations for midges are not similarly elevated. Notably, studies have found high MeHg concentrations in Icelandic lamb (Reykdal and Thorlacius 2001) and mosses (Ru¨hling and Steinnes 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon could explain why, despite the remoteness and low industrial activity in northeastern Iceland, MeHg concentrations in terrestrial arthropods are elevated, although it is unclear why MeHg concentrations for midges are not similarly elevated. Notably, studies have found high MeHg concentrations in Icelandic lamb (Reykdal and Thorlacius 2001) and mosses (Ru¨hling and Steinnes 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, if inadequate equipment is used to conduct the acid digestion, unacceptable losses of analytes such as As and Hg may arise by volatilization. The widespread use of microwave assisted acid digestion with elevated pressure and temperature control has alleviated these problems [2,4,[7][8][9][10][12][13][14]17,20,[27][28][29]32,[35][36][37][38]41,43,[45][46][47][48][50][51][52][53][54][55][56][57][59][60][61][62][64][65][66]69,[71][72][73]76] and enabled the use of large sample masses (1-2 g) without the danger of vessel rupture and with a minimal chance for contamination. Microwave assisted processes are particularly important when the determination of As and Hg is targeted as complete mineralization of the sample can be achieved at low temperature preventing losses of these elements.…”
Section: Acid Digestionmentioning
confidence: 99%
“…Matrix destruction based on oxidation with concentrated acids is the most widely used approach for biological samples because of its efficiency [1][2][3][4][6][7][8][9][10][11][12][13][14][15][16][17]20, (Table 1) in liberating the elements of interest from the molecular structures. Analyses of the resultant digest by ETAAS have several advantages: ease of manipulating the analyte concentrations to be in the optimum range of detection, availability of appropriate calibration standards and the use of less sophisticated instrumentation.…”
Section: Acid Digestionmentioning
confidence: 99%
See 2 more Smart Citations